Predictors of Chronic Energy Deficiency in Urban Geriatric Population: Findings from Community Based Study. - Keshari, Priya; Shankar, Hari (Online Journal of Health & Allied Sciences)
Background/Objectives: Increased longevity and declining fertility have increased the number of older population globally. Several factors make older population vulnerable to malnutrition. The purpose of this study was to find out predictors of Chronic Energy Deficiency (CED) of geriatric subjects. Materials and Methods: This study was conducted on 616 urban subjects (≥ 60 years) by adopting community based cross sectional design. Socioeconomic characteristics of the subjects was obtained by interviewing them using interview schedule. Their weight and height were recorded following standard technique. A subject with Body Mass Index <18.5 kg/m2 was considered as victim of CED. Data analysis was done using SPSS version 22.0. For inferential purpose Adjusted Odds Ratios and 95% Confidence Interval were computed. Results: In all 44.8% subjects had CED. Age, religion, literacy status, and Socio Economic Status emerged as predictors of CED. Adjusted Odds Ratio (AOR) for CED was 4.05 (95% CI: 1.52- 10.77) in > 80 years and 2.20 (95%CI: 1.4-4.43) in 70-79 years age group. AOR for Muslims was 2.16 (95%CI: 1.31-3.56) for CED. Taking educational status intermediate and above as reference AOR for CED for illiterate and just literate was 2.53(95% CI: 1.10-5.81) and for primary plus middle was 2.42(95%CI 1.08-5.44). For subjects from lower socio economic status AOR was 1.74(95%CI: 1.02-2.96). Conclusion: Age, religion, literacy status and socioeconomic status were predictors of CED in geriatric subjects.